Comparison of the Effectiveness of Cognitive Behavioral Therapy and Intensive Short-Term Dynamic Psychotherapy on Conflict Resolution Styles and Cognitive Flexibility in Incompatible Couples - Bagheri, Sareh; Hosseini Harandehi, Seyedeh Fatemeh (KMAN Counseling & Psychology Nexus, 2025)
The present study aimed to compare the effectiveness of Cognitive Behavioral Therapy (CBT) and Intensive Short-Term Dynamic Psychotherapy (ISTDP) on conflict resolution styles and cognitive flexibility in incompatible couples. This study employed a quasi-experimental design with a pre-test–post-test structure including a control group and two experimental groups. The statistical population consisted of all incompatible couples who sought services from family counseling centers in Garmsar in 2024. From this population, 40 couples (80 individuals) were selected through purposive sampling based on specific inclusion and exclusion criteria and were then randomly assigned to three groups: 14 couples in the CBT group, 13 couples in the ISTDP group, and 13 couples in the control group. Data collection instruments included the Marital Conflict Questionnaire (Zaker & Barati, 2008) and the Cognitive Flexibility Inventory (Dennis & Vander Wal, 2010). Therapeutic interventions were conducted over eight sessions based on the Dattilio (2010) protocol for CBT and the Davanloo (2000) protocol for ISTDP. Data analysis was performed using the Shapiro–Wilk test, Levene’s test, and Multivariate Analysis of Covariance (MANCOVA) via SPSS version 27. The results indicated a significant difference between the pre-test and post-test scores in the experimental groups for the variables of marital conflict and cognitive flexibility (p ≤ 0.001), whereas no significant differences were observed in the control group. Additionally, post-test comparisons revealed significant differences between the treatment groups and the control group for both variables (p ≤ 0.001); however, no statistically significant difference was found between the two treatment groups. Based on the findings, CBT was more effective in reducing marital conflict due to its higher effect size, whereas ISTDP had a greater impact on enhancing cognitive flexibility in couples.